2021
DOI: 10.1186/s13148-021-01028-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular health and epigenetic age acceleration

Abstract: Background Cardiovascular health (CVH) has been defined by the American Heart Association (AHA) as the presence of the “Life’s Simple 7” ideal lifestyle and clinical factors. CVH is known to predict longevity and freedom from cardiovascular disease, the leading cause of death for women in the United States. DNA methylation markers of aging have been aggregated into a composite epigenetic age score, which is associated with cardiovascular morbidity and mortality. However, it is unknown whether p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“… 26 , 27 Pottinger and his colleagues observed that poor cardiovascular health was associated with the epigenetic age acceleration in a cross‐sectional analysis of 2170 menopausal women. 28 In the present study, an increase in epigenetic age acceleration per 10–mm Hg of blood pressure was found to be <1 year. Several cardiometabolic risk factors pose threats to the premature decline of physical functioning attributable to accelerated aging, and blood pressure may play a small part in such declines.…”
Section: Discussionsupporting
confidence: 41%
“… 26 , 27 Pottinger and his colleagues observed that poor cardiovascular health was associated with the epigenetic age acceleration in a cross‐sectional analysis of 2170 menopausal women. 28 In the present study, an increase in epigenetic age acceleration per 10–mm Hg of blood pressure was found to be <1 year. Several cardiometabolic risk factors pose threats to the premature decline of physical functioning attributable to accelerated aging, and blood pressure may play a small part in such declines.…”
Section: Discussionsupporting
confidence: 41%
“…[21,66,69] Epigenetic age may be a useful biomarker for CVD risk and provide a biological perspective on the role of epigenetic mechanisms in age-related CVD loss and CVDs. [70][71][72] GrimAge can predict CVD risk not only for White people, but also for African Americans. [73] The DNA methylation aging clock is also currently used as a biomarker for other diseases, such as stroke, Alzheimer disease, and cancer.…”
Section: Application Of Epigenetic Clocks In Cvdsmentioning
confidence: 99%
“…Likewise, Beach et al (2016) [28] found that childhood SES-risk was associated with widespread changes in methylation in young adulthood. Focusing more specifically on cardiometabolic health outcomes, it was reported recently that better cardiovascular health practices were associated with decreases in age acceleration on indices developed by Horvath [24] and Hannum [25], and effects were robust to calculations of intrinsic AA for both clocks [29].…”
Section: Intrinsic Dna Methylation Based Ageingmentioning
confidence: 99%